Petri Net Approach for Estimation the Information Systems Security Level in Any Logic Environment - Tun, Hein; Lupin, Sergey; Oo, Ko Ko; Oo, Myat Min (2019 53rd Annual Conference on Information Sciences and Systems (CISS), 2019)
At present, the security of information system is becoming one of the biggest challenges for all organizations. Information security is the protection of information and systems from unauthorized access, use, disclosure, modification, destruction in order to provide confidentiality, integrity, and availability. In this article, we discuss the methodology for estimating the security of information systems based on hybrid modeling in the Any Logic environment. A conceptual model of the information protection system is described in this paper. Moreover, a data structure that allows the behavior of agents to access the information system is presented here.